Rost mirovoy promyshlennosti k nachalu XX veka (ОГИЗ - Госполитиздат (State Publishing House), 1957)
Informational charts depicting division of global industry at the beginning of the 20th century Original title: Рост мировой промышленности к началу ХХ века PO-0633